Resistance in lentil (Lens culinaris) genetic resources to the pea aphid (Acyrthosiphon pisum). Issue 8 (4th July 2022) - Das, Shimul; Porter, Lyndon D.; Ma, Yu; Coyne, Clarice J.; Chaves‐Cordoba, Bernardo; Naidu, Rayapati A.
Abstract: The pea aphid (PA), Acyrthosiphon pisum (Harris) (Hemiptera: Aphididae), can cause complete yield loss in lentil, Lens culinaris Medik. (Fabaceae, Leguminosae), if not managed properly. Determining lentil genetic resources with resistance to PA is important for integrated pest management (IPM) in production areas worldwide. The objectives of this study were to identify genetic resources and genes associated with resistance to PA in 188 lines of the USDA Lentil Single Plant Core Collection. A cluster analysis of the mean number of adults, nymphs, and total aphids that developed on lentil lines 10 days after infestation with a single aphid identified four clusters associated with aphid resistance: 20 lines were considered resistant, 99 moderately resistant, 51 moderately susceptible, and 18 susceptible. PIs 329157 LSP and 432085 LSP, originating from Iran, demonstrated the best resistance when assessing antibiotic and antixenotic properties. Genotyping‐by‐sequencing (GBS)‐based single nucleotide polymorphisms (SNPs) were used for genome‐wide association mapping to locate genes or quantitative trait loci (QTL) associated with PA resistance traits, in which six, four, and three SNPs were associated with low numbers of PA adults, nymphs, and total aphids that developed on lentil lines, respectively. Fifteen candidate genes were identified relating to PA resistance. The results can effectively be used in molecular lentil breeding programs to target specific genomic regions associated with PA resistance, as well as in traditional breeding, using lines identified as highly PA‐resistant as parents, to develop durable resistance in lentil cultivars. Abstract : The pea aphid (PA), Acyrthosiphon pisum (Hemiptera: Aphididae), can cause complete yield loss in lentil, Lens culinaris (Fabaceae, Leguminosae), if not managed properly. Resistance is important for integrated pest management (IPM). We identified genetic resources and genes associated with resistance to PA in 188 lentil lines. Overall, 20 lines were resistant, 99 moderately resistant, 51 moderately susceptible, and 18 susceptible. In a genome‐wide association study (GWAS), 15 candidate genes were identified. The results may be used in lentil breeding programs.